Effects of a Combination of Arginine Silicate Inositol Complex and a Novel Form of Biotin on Hair and Nail Growth in a Rodent Model - Demir, Betul; Cicek, Demet; Orhan, Cemal; Er, Besir; Erten, Fusun; Tuzcu, Mehmet; Şahin, Kazım (Springernature, 2023)
The purpose of this study was to examine the effects of a combination of inositol-stabilized arginine silicate complex (ASI) and magnesium biotinate (MgB) on hair and nail growth in an animal model. Twenty-eight female Sprague-Dawley rats (8 weeks old) were randomized into one of the following groups: (i) group (control), shaved; (ii) group (ASI), shaved + ASI (4.14 mg/rat/day); (iii) group (ASI + MgB I), shaved + ASI (4.14 mg/rat/day) + MgB (48.7 mu g/rat/day); and (iv) group (ASI + MgB II), shaved + ASI (4.14 mg/rat/day) + MgB (325 mu g/rat/day). On day 42, compared with the control group, while hair density (p < 0.05, p < 0.01, and p < 0.0001, respectively) and anagen ratio (p < 0.01, p < 0.01, and p < 0.001) increased in the ASI, ASI + MgB I, and ASI + MgB II groups, telogen ratio decreased (p < 0.01, p < 0.01, and p < 0.001, respectively). In the molecular analysis, VEGF, HGF, and KGF-2 increased in the ASI (p < 0.01, p < 0.01, and p < 0.05, respectively), ASI + MgB I (p < 0.0001 for all), and ASI + MgB II (p < 0.0001 for all) groups when compared to the control group. FGF-2 (p < 0.01) and IGF-1 (p < 0.001) were found to be increased in the ASI + MgB I and ASI + MgB II groups. SIRT-1 and beta-catenin increased in the ASI (p < 0.05 and p < 0.01), ASI + MgB I (p < 0.001 for both), and ASI + MgB II (p < 0.0001 for both) groups. Wnt-1 increased in the ASI + MgB I (p < 0.001) and ASI + MgB II (p < 0.0001) groups. In conclusion, the combination of ASI and MgB could promote hair growth by regulating IGF-1, FGF, KGF, HGF, VEGF, SIRT-1, Wnt, and beta-catenin signal pathways. It was also established that ASI did not affect nail growth, whereas the MgB combination was effective using a higher dose of biotin.
Keywords: Arginine silicate; Biotin; Hair; Magnesium; Nail